Impact of preoperative fasting duration and prostate mass on postoperative bleeding after transurethral enucleation of the prostate: A risk factor analysis - Zihui Gao; Jiazhao Cui; Chunji Wang (Journal of International Medical Research)
Objective This study explored the impact of preoperative fasting duration on patients who underwent transurethral enucleation of the prostate and analyzed the risk factors for postoperative bleeding. Methods A retrospective analysis was conducted among 51 patients who underwent transurethral enucleation of the prostate for benign prostatic hyperplasia between December 2021 and March 2024. Baseline and perioperative data were collected. The impact of long versus short preoperative fasting was compared. Univariate and multivariate logistic regression analyses were used to identify risk factors for bleeding complications after transurethral enucleation of the prostate. Results The mean hemoglobin difference in the short fasting group was 14.43 ± 11.23 g/L, while that in the long fasting group was 17.21 ± 12.21 g/L, showing a statistically significant difference (p = 0.048). The mean postoperative hospital stay was 3.39 ± 1.05 days in the short fasting group and 4.21 ± 1.68 days in the long fasting group, showing a statistically significant difference (p = 0.047). Univariate and multivariate regression analyses identified prostate mass (p = 0.045) and preoperative fasting duration (p = 0.033) as independent risk factors for postoperative bleeding in patients who had undergone transurethral enucleation of the prostate. Conclusion Patients who had undergone transurethral enucleation of the prostate after longer preoperative fasting experienced a more significant decline in hemoglobin levels and required longer postoperative hospitalization. Prostate mass and preoperative fasting duration were identified as independent risk factors for postoperative bleeding after transurethral enucleation of the prostate.